The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1021/acsami.8b13249
|View full text |Cite
|
Sign up to set email alerts
|

Intelligent Biomimetic Chameleon Skin with Excellent Self-Healing and Electrochromic Properties

Abstract: Animals such as chameleons possess a natural ability to adjust their skin color as a preventive measure to deter any potential threat and to self-heal damaged skin tissues. Inspired by this, we present here a copolymer film possessing biomimetic properties that simultaneously integrates electrochromic triphenylamine and self-healing Diels-Alder groups. The flexible and stretchable copolymer film acts like natural chameleon skin, which exhibits significant color variation and also possesses excellent self-heali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 30 publications
(54 reference statements)
1
44
0
Order By: Relevance
“…In recent times, inspired by "Chameleons" for self-healing nature of their damaged skin tissue and ability to adjust their skin colour, very recently Zheng et.al [185] 2018, designed the bifunctional DFTPA-PI-MA copolymer film possessing chameleons like biomimetic properties by integrating electrochromic diphenylamine and self-healing DA groups into the polymer matrix, as shown in Figure 19. The authors concluded that the electroactive TPA group and the reversible DA cross-linking imparted electrochromic and self-healing performance in a single film with a fast switching for color response and excellent self-healing efficiency of about 90%.…”
Section: Diels-alder (Da) Reactionmentioning
confidence: 99%
“…In recent times, inspired by "Chameleons" for self-healing nature of their damaged skin tissue and ability to adjust their skin colour, very recently Zheng et.al [185] 2018, designed the bifunctional DFTPA-PI-MA copolymer film possessing chameleons like biomimetic properties by integrating electrochromic diphenylamine and self-healing DA groups into the polymer matrix, as shown in Figure 19. The authors concluded that the electroactive TPA group and the reversible DA cross-linking imparted electrochromic and self-healing performance in a single film with a fast switching for color response and excellent self-healing efficiency of about 90%.…”
Section: Diels-alder (Da) Reactionmentioning
confidence: 99%
“…Although the previously described systems are very useful for displaying information for soft robots, it is crucial for the color-changing devices to self-heal as the above-described systems experience large deformation constantly. Inspired by the chameleon, self-healable and stretchable color-changing devices based on photonic elastomer [276] or electrochromic devices [277] were developed, using self-healing substrates to achieve the self-recovery upon damage.…”
Section: Display Screen and Lightingmentioning
confidence: 99%
“…Electrochromic triphenylamine and self‐healing Diels–Alder groups were copolymerized to provide electrochromic, and self‐healing properties like an intelligent “chameleon skin.” [ 67 ] However, the transparency of the device was poor and the color contrast was too low to be applied in a smart window.…”
Section: Electrochromism In Conjugated Polymersmentioning
confidence: 99%